Evaluating the effectiveness of COVID-19 vaccines in adults with sickle cell disease during the Omicron period of COVID-19 pandemic - Aldecoa, Kim Abbegail Tan; Macaraeg, Chef Stan L.; Arsene, Camelia; Krishnamoorthy, Geetha; Chng, Tiffany; Cherry, Garrett; Chowdhury, Nabila; Clark, Ryan; Deeb, Dana; Deptula, Lisa; Dietz, Grey; Eto, Ewomamobuho; et al. (Frontiers in Hematology, 2024)
Background and aimsThe Omicron variant, one of the variants causing the coronavirus disease of 2019 (COVID-19), was first identified in November 2021 and became the predominant variant in 2022. Although causing less severe disease, this variant and its subvariants have been associated with increased transmissibility and limited protection despite vaccination and prior infection. Individuals with sickle cell disease (SCD) are particularly at greater risk of severe illness and death, and studies regarding the effectiveness of COVID-19 vaccination have been limited in this population. The study aims to determine the effectiveness of COVID-19 vaccination during this period among individuals with SCD and to examine various factors that can influence the likelihood of COVID-19 infection and severity among SCD individuals.MethodsThis is a retrospective analysis of adult patients (≥18 years) with SCD who had emergency and inpatient encounters between January 1 and December 31, 2022. Multivariable regression analysis was performed to determine the effectiveness of the COVID-19 vaccine among this population.ResultsThe study found that COVID-19 vaccination lowered the infection risk among SCD individuals by over 70% if they have received at least one dose of the vaccine. The study also found that individuals with SCD and a history of acute chest syndrome were over 3 times more likely to have a COVID-19 infection diagnosis than those without a history of acute chest syndrome.ConclusionThe study confirms the effectiveness of the COVID-19 vaccine among individuals with SCD during the Omicron period of the COVID-19 pandemic.